A Class of Polynomials From Enumerating Queen Paths - Goswami, Ashish; Tran, Khang (The PUMP Journal of Undergraduate Research, 2025)
We study a class polynomials obtained from an enumeration of the number of queen paths. In particular, we find the generating function for the diagonal sequence of this table and the zero distribution of a sequence of related polynomials.